Fıxed Anterıor Reposıtıonıng Splınt - Enis Güray; Serdar Üşümez; Fatih Öz (Galenos Yayinevi, 2002)
This paper aims to describe a new type of anterior repositioning splint, which can be used for the anterior repositioning of the mandible in cases with acute closed lock of temporomandibular joint in non-compliant patients. A nineteen year old female patient that present an acute dislocation of the condylar disc without reduction secondary to para-functional activity underwent splint therapy with the "Fixed Anterior Repositioning Appliance (FARA)" following recapture of the disc with functional manoeuvre. Pre and post-treatment magnetic resonance imaging of temporomandibular joint is presented. The FARA prevented the disc from unintentional dislocation, which is possible with wide mouth opening. The disc was hold and retained in the musculoskele-tally stable position at 6-month follow-up. The new appliance can serve as a comfortable alternative to conventional anterior repositioning splints.